Androgen annihilation versus advanced androgen blockage as first line treatment for metastatic castration resistant prostate cancer: A systematic review and meta-analysis. (November 2022) - Fallara, Giuseppe; Belladelli, Federico; Robesti, Daniele; Raggi, Daniele; Nocera, Luigi; Marandino, Laura; Galsky, Matthew D.; Montorsi, Francesco; Malavaud, Bernard; Ploussard, Guillaume; Necchi, Andrea; Martini, Alberto
Abstract: Background: Despite recent advances in the treatments of metastatic castration resistant prostate cancer (mCRPC), patients' prognosis remains suboptimal and novel treatment combinations are under scrutiny. On this matter, the recent ACIS trial tested the role of abiraterone plus apalutamide (androgen annihilation) in addition to androgen deprivation therapy, versus abiraterone plus androgen deprivation therapy. Herein, we performed a meta-analysis to compare overall survival (OS) and progression free survival (PFS) among patients who received androgen annihilation versus advanced androgen blockage (abiraterone or enzalutamide), in addition to conventional androgen deprivation therapy. Methods: A comprehensive search for all published phase III randomized control trials on first line mCRPC that evaluated advanced androgen blockage (COU-AA-302, PREVAIL) or androgen annihilation (ACIS) was conducted PubMed, EMBASE, Web of Science, and Scopus databases up to 31/12/2021. We reconstructed survival data from published Kaplan-Meier curves on overall survival (OS) and progression free survival (PFS) and meta-analyzed androgen annihilation versus advanced androgen blockage (grouping together abiraterone and enzalutamide) versus androgen deprivation therapy. The outcomes of interest were assessed using difference in restricted mean survival time (ΔRMST) at different time points. Results: Three trials were included involving 3787 patients. Overall, patients receiving androgen annihilation exhibited similar OS compared to advanced androgen blockage: ΔRMST at 36 months of − 0.2 (95%CI: −1.1, 0.8, p = 0.8). At 36 months, relatively to ADT alone, patients receiving androgen annihilation or advanced androgen blockage exhibited longer OS: ΔRMST of 1.6 (95%CI: 0.6, 2.7, p = 0.002) and 1.8 months (95%CI: 1.1, 2.5, p < 0.001), respectively. Patients receiving androgen annihilation exhibited better PFS compared to advanced androgen blockage: ΔRMST at 36 months of 2.4 months (95%CI: 1.0, 3.8, p = 0.001). Conclusion: We found no OS benefit for patients with mCRPC treated with androgen annihilation compared to advanced androgen blockage. This might be ascribed to an increased rate of other cause mortality that might determine the absence of an OS benefit or to the efficacy of second line therapies. Optimal treatment sequence and patient selection for androgen annihilation remain open points. However, a PFS benefit was found in case of combination therapy, whose clinical meaning is not yet clear. Graphical Abstract: ga1 Highlights: Despite recent advances in treating metastatic castration resistant prostate cancer, patients' prognosis remains suboptimal and novel treatment combinations are under scrutiny. Presently there is a lot of interest on combination therapies in the form of "triplets". The recently published ACIS trial investigated androgen annihilation [AA] versus advanced androgen blockage [AAB] in addition to conventional ADT. In this Meta-analysis we aimed to compare the effectiveness of AA versus AAB versus ADT. We relied on the difference in restricted mean survival time (Δ RMST) for OS and PFS comparison. Patients receiving AA exhibited better PFS compared to AAB. Yet, we found no OS benefit for AA compared to AAB. This might be ascribed to an increased rate of other cause mortality that might determine the absence of an OS benefit or to the efficacy of second line therapies.